2007
DOI: 10.1038/sj.ejhg.5201790
|View full text |Cite
|
Sign up to set email alerts
|

Undergoing prenatal screening for Down's syndrome: presentation of choice and information in Europe and Asia

Abstract: To date, studies assessing whether the information given to people about screening tests facilitates informed choices have focussed mainly on the UK, US and Australia. The extent to which written information given in other countries facilitates informed choices is not known. The aim of this study is to describe the presentation of choice and information about Down's syndrome in written information about prenatal screening given to pregnant women in five European and two Asian countries. Leaflets were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…These 2 countries are different in terms of attitudes about individualism and collectivism 36 . Cultures that stress individual contributions to society within a collectivistic standpoint are more likely to have more influence on women's decisions 36 and to provide fewer resources as well as negative information for the family and individuals with disabilities 37 . Moreover, women who choose to continue their pregnancies with DS in these societies may be considered to be responsible for all care concerning their child with DS because they elected to have the child 38…”
Section: Discussionmentioning
confidence: 98%
“…These 2 countries are different in terms of attitudes about individualism and collectivism 36 . Cultures that stress individual contributions to society within a collectivistic standpoint are more likely to have more influence on women's decisions 36 and to provide fewer resources as well as negative information for the family and individuals with disabilities 37 . Moreover, women who choose to continue their pregnancies with DS in these societies may be considered to be responsible for all care concerning their child with DS because they elected to have the child 38…”
Section: Discussionmentioning
confidence: 98%
“…Studies in countries where prenatal screening is performed as routine prenatal care show that it is generally expected that women will participate in testing. A comparative study on the offer of prenatal screening showed that choice was mentioned only briefly or not at all in most of the leaflets (Lawson, 2003;Hall et al, 2007;Gottfrejsdó ttir et al, 2009). In these countries, the rates of termination of pregnancy for fetal anomaly following prenatal testing are high (EUROCAT, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To this extent, many of the issues raised above are also relevant in the context of national screening programmes. Additional factors to be taken into consideration might include evidence that norms and standard practice may be culturally determined: for example, a comparison of written information provided to those undergoing carrier screening for cystic fibrosis suggested a more positive description of the condition in the US than the UK [58,59]. This suggests that particular care is needed to ensure that key concepts are communicated effectively, particularly as empirical research using vignettes comparing the impact of invasive testing with non-invasive prenatal testing and Down’s syndrome screening suggest that health professionals regard the need for time for reflection and written consent to be less compelling in women undergoing non-invasive prenatal testing or Down’s syndrome screening (with around 20–25% of those questioned regarding less need for the test offer and uptake to be on different days or a signed consent form obtained) [60,61,69].…”
Section: Ethical Legal and Social Implicationsmentioning
confidence: 99%